Variabilidade espacial tridimensional dos atributos químicos e físicos de frutos em pomar de laranjas - Gasparin, Eloi (2013)
The increase in production and yield as well as the correct use of agricultural inputs are essential factors to be taken into consideration when thinking about modern agriculture. Several techniques, previously used, mainly in the mining sector, have been incorporated to the agricultural sector with the precision agriculture management. The orcharding has also been improved by several studies under development in order to make such sector more competitive both nationally and internationally. The physical and chemical characteristics of orange fruits may change depending on the conditions to which they are exposed to, up from their blossoming period until harvest. Such conditions can be both climatic and related to the fruit position on the treetop. Although good fruit appearance is important, physical and chemical characteristics are as well, both for fresh consumption and industrial processing. Thus, this trial aimed at studying the three-dimensional spatial variability of physical and chemical characteristics of orange fruits in orchards, based on the generation of threedimensional maps and the SGeMS software. The trial was carried out in an orchard with Monte Parnaso orange variety, in Nova Laranjeiras city, Paraná, whose average altitude is 760 m and UTM central coordinates are around 7191655 m S and 341660 m E, 22J. So, 715 orange fruits from nine trees were analyzed during 2011, 2012 and 2013. Physical and chemical parameters showed weak correlation according to their position on the tree, but there was a trend of increasing values concerning the following attributes: diameter, fruit weight and juice mass as the vertical position of the fruits increases. For TSS content, the highest values were observed in the peripheral area of the tree and in its apical third part; but, for TTA content, it tended to decrease with the increasing vertical position of fruit. At last, the applied methodology was appropriate for the three-dimensional study concerning physical and chemical characteristics of orange fruits